Efficacy and safety of short-term 1–3 months versus standard 12 months dual antiplatelet therapy in patients undergoing percutaneous coronary intervention: a meta-analysis of randomized clinical trials. (4th July 2021) - Zhang, Wen-Jiao; Qiao, Xuan; Liang, Xi-Ying; Li, Yan; Yang, Rong-Rong; Wang, Zhi-Lu
Abstract: Dual antiplatelet therapy (DAPT) is the basis of preventing stent thrombosis and ischemic events after percutaneous coronary intervention (PCI), but prolonging the duration of DAPT will increase the risk of bleeding. The optimal duration of DAPT after PCI remains controversial at present. The purpose of this meta-analysis was to investigate the efficacy and safety of short-term DAPT in patients undergoing PCI. PubMed, Embase, Cochrane and Web of science from inception to September 2019 were systematically searched. Randomized controlled trials were included to compare short term (3 months or less) with a standard 12-months DAPT in patients undergoing PCI. Random effect model and fixed effect model wereused to calculate the risk ratio (RR) and 95% confidence interval (CI) of each endpoint. This meta-analysis included 38479 patients undergoing PCI from 8 randomized clinical trials. No difference was observed in the risk of all-cause death (RR 0.92, 95% CI 0.80–1.06, P = 0.25), cardiovascular death (RR 0.88, 0.69–1.12, P = 0.29), myocardial infarction (RR 1.05, 0.94–1.19, P = 0.38), definite or probable stent thrombosis (RR 1.05, 0.80–1.36, P = 0.73), and stroke (RR 1.02, 0.80–1.30, P = 0.89) between short term and standard DAPT. The short-term DAPT could reduce the risk of major bleeding (RR 0.67, 0.48–0.94, P = 0.02) and any bleeding (RR 0.63, 0.48-0.82, P = 0.0005) compared with 12 months of DAPT. In conclusion, the short-term DAPT can reduce the risk of bleeding compared with standard DAPT, without increasing the risk of death or ischemia (Registered by PROSPERO, CRD42020153881).